Applications of advanced analytical and mass spectrometry techniques to the characterisation of micaceous lithium-bearing ores. (15th January 2018) - Aylmore, Mark G.; Merigot, Kelly; Quadir, Zakaria; Rickard, William D.A.; Evans, Noreen J.; McDonald, Bradley J.; Catovic, Enej; Spitalny, Peter
Highlights: Advanced analytical microscopy and mass spectrometry used to characterize Li minerals. Micas classified based on their compositions to distinguish different Li mica grades. Majority of Li in samples associated with lepidolite or zinnwaldite particles. Lepidolite and zinnwaldite made up of Li muscovite, trilithionite and polylithionite. At P100  = 4 mm the majority of Li mica particles were liberated from gangue minerals. Fine grinding required to liberate fine Li mica minerals for further treatment. Factors which need to be considered in treating and processing Li micas are discussed. Abstract: With the impetus for less reliance on fossil fuels and an increasing demand for environmentally friendly energy materials, lithium is emerging as an important material of the future. The ability to extract lithium from ores economically is essential. However, a comprehensive understanding of the deportment of lithium and associated minerals in some ore bodies is limited. A combination of analytical microscopy and mass spectrometry techniques has been used to allow detection and characterisation of different lithium minerals in three micaceous Li-bearing ores. To quantify the different Li-bearing ore minerals, the chemistry and structural characteristics of a suite of lithium mineral specimens were first examined. The micas can be classified and grouped based on their compositions (Al/Si ratio; F, Na content) and used to distinguish different micas with different lithium grades. Micas exist as different polymorphs that are generally related to composition and also geological environment. The mineralogy, mineral associations and liberation characteristics of both ore-bearing and gangue minerals were characterised using automated mineralogy techniques and the Li content and elemental distribution within minerals defined using instrumentation with secondary mass spectrometry capabilities. The majority of lithium in the ore samples (1.2–1.5% Li) examined is associated with lepidolite or zinnwaldite particle compositions which are made up of Li muscovite, trilithionite and polylithionite grains. The morphology of the Li-bearing micas varies in different deposits. The gangue materials are predominately quartz and albite and make up ≤20 w% of the sample. Only minor amounts (∼1%) of other Li-bearing minerals (e.g. spodumene, elbaite, beryl) were observed in these samples. The Ta grade associated with minerals rynersonite and columbite-tantalite in some samples may be economic. The majority of the Li mica particles were liberated from the major gangue minerals under the conditions used to treat and screen samples to pass a 4 mm sieve. Further grinding will be required to breakup and expose fine grains of Li muscovite, polylithionite, and trilithionite, for further treatment to extract Li. The processes used to breakdown the micas to extract Li will also require stabilising and removal of F, Fe, Al, Mn and monovalent ions K and Na from process streams. The high concentration of Rb (0.9–3.6 wt%) and Cs (0.1–0.8 wt%) make mica a favourable resource for these elements and they can ultimately be recovered along with Li.